Relationships among Calibrachoa, Fabiana and Petunia (Petunieae tribe, Solanaceae) and a new generic placement of Argentinean endemic Petunia patagonica - Alaria, Alejandrina Soledad (2022)
Calibrachoa Cerv., Fabiana Ruiz & Pav., and Petunia Juss. form a clade within tribe Petunieae (Solanaceae). Phylogenetic studies of Petunieae, either as part of a family-wide analysis or focusing on the genera Calibrachoa and Petunia, have either left Fabiana unsampled or included only a single species. These studies have found conflicting relationships among the three genera with all three possible topologies obtained. Petunia patagonica (Speg.) Millán, originally described in the genus Nierembergia Ruiz & Pav., is morphologically distinct within Petunia and geographically disjunct from other members of the genus. For the first time, in this study we include multiple species of Fabiana, Calibrachoa, and Petunia, including P. patagonica. Using three chloroplast DNA regions and the nuclear gene GBSSI, or “waxy,” our results provide strong support for a sister group relationship between Calibrachoa and Fabiana and for the placement of P. patagonica within Fabiana. Since there is already a species Fabiana patagonica Speg., we provide the new name Fabiana australis Alaria nom. nov. to replace Petunia patagonica.